Absorption and cleavage of enalapril, a carboxyl ester prodrug, in the rat intestine: in vitro, in situ intestinal perfusion and portal vein cannulation models. (4th May 2015) - Holenarsipur, Vinay K.; Gaud, Nilesh; Sinha, Jaydeep; Sivaprasad, Sankara; Bhutani, Priyadeep; Subramanian, Murali; Singh, Sheelendra Pratap; Arla, Rambabu; Paruchury, Sundeep; Sharma, Tarun; Marathe, Punit; Mandlekar, Sandhya
Abstract In recent years prodrug strategy has been used extensively to improve the pharmacokinetic properties of compounds exhibiting poor bioavailability. Mechanistic understanding of the absorption and the role of intestine and liver in the activation of oral prodrugs is crucial. Enalapril, a carboxyl ester prodrug, is reported to be metabolized by human carboxylesterase‐1 (CES1) but not by carboxylesterase‐2 (CES2) to its active metabolite enalaprilat. Further, it has been reported that the small intestines of both rat and human contain mainly CES2. The objective of this work was to understand whether enalapril remains unchanged as it is absorbed through the intestine into the portal circulation. This was evaluated using different intestinal preparations, an in situ intestinal perfusion experiment and a portal vein cannulated rat model. No turnover of enalapril was seen with commercial rat intestinal S9 and microsomes, but reasonable turnover was observed with freshly prepared rat intestinal and mucosal homogenate and S9. In the intestinal perfusion study, both enalapril and enalaprilat were observed in the mesenteric plasma with the data suggesting 32% hydrolysis of enalapril in the intestine. In the portal vein cannulated rat, about 51% of enalapril absorbed into intestine was converted to enalaprilat. Overall, it was demonstrated that even though enalapril has been shown to be a specific substrate for CES1, it is converted to enalaprilat to a significant extent in the intestine. Such experimental techniques can be applied by other scientific groups who are working on prodrugs to determine the region and extent of activation. Copyright © 2015 John Wiley & Sons, Ltd.